Integration in health: cooperation at triple international border Amazon - Giane Zupellari dos Santos-Melo; Selma Regina de Andrade; Betina Hörner Schlindwein Meirelles; Angela Maria Blatt Ortiga (Universidade de São Paulo, 2020)
ABSTRACT OBJECTIVE: To describe the scope and limitations of the main strategies of cooperation in health, adopted between 2005 and 2017, in the context of the triple border Brazil, Colombia and Peru. METHOD: Single, explanatory, qualitative, integrated case study carried out in 2017, in the context of the triple Amazon border, Brazil, Colombia and Peru, in the city of Tabatinga, state of Amazonas, Brazil. Our sources of evidence were: documentary data; interviews with health managers of the State Health Secretariats of Amazonas and Municipal Health of Tabatinga, Municipal Health Council of Tabatinga and Consulate of Peru in Colombia; and direct observations in four health services of Tabatinga. Data were organized with MaxQDA12® software. RESULTS: Data analyzed showed that, during the study period, the Brazilian federal government made several health cooperation agreements with both Peru and Colombia and that the state government of Amazonas undertook strategies to improve the health conditions of the dwellers of Tabatinga and the region of Alto Solimões, which indirectly reached the populations of neighboring countries, supporting the interrelationships between the countries of the region. Regarding the municipal government, we verified the existence of health integration agreements, established informally, to minimize the adversities of the local health. CONCLUSION: The cooperation strategies in health adopted in the triple Amazon border have different purposes, benefits and limitations. It is noteworthy that the existence of cooperation agreements between the federal governments of Brazil, Colombia and Peru and the presence of informal cooperation agreements between the municipal governments of Tabatinga (Brazil), Leticia (Colombia) and Santa Rosa (Peru). The limitations of this study are the lack of knowledge of local managers about the cooperation agreements established between federal governments and the lack of legitimacy of the informal agreements established by the Tabatinga government.